Finite Element Analysis of Ring Force Transducer. (November 2019) - Saxena, Richa; Kumar Ghoshal, Sanjoy; Kumar, Harish; Arora, P K
Abstract: Ring shaped force transducer have been used for different industrial and metrological applications for about one century since inception at National Institute of Standards and Technology (formerly, National Bureau of Standards), USA. Though, earlier they have been equipped with deflection measuring device say, micrometre, dial gauge or vibrating reed as the case may be. With growing advancement, to limit the inherent shortcomings of analogue instruments, digitization has been done over the past decades. In this regard, few research reports have been published, but up to best of knowledge of the authors, realistic computational investigations are still missing. In past findings, there have been limitations either with coherence with experimental findings or limits of the software used for the investigations. In this regard, commercial software ANSYS has been used for complete ring shaped force transducer and a realistic procedure adopted in line with analytical method. The present study attempts to discuss the procedure and outcome of finite element analysis for a ring shaped force transducer for the material EN 24 with a nominal capacity of 50 kN. The paper discusses details of the approach adopted and salient outcomes. The paper further discusses the implications of the finite element analysis in design and development of the ring shaped force transducer.